Who's up to the challenge? 48

Calculus Level 5

0 1 x H x d x = a + γ b ln c π \large \int _{ 0 }^{ 1 }{ x{ H }_{ x }\, dx } =a+\dfrac { \gamma }{ b } -\ln { \sqrt { c\pi } }

If the equation above holds true for positive integers a , b a,b and c c , find a + b + c a+b+c .

Notations :

  • H n H_n denotes the n th n^\text{th} harmonic number , H n = 1 + 1 2 + 1 3 + + 1 n H_n = 1 + \dfrac12 + \dfrac13 + \cdots + \dfrac1n .

  • γ \gamma denotes the Euler-Mascheroni constant , γ 0.5772 \gamma \approx 0.5772 .


The answer is 5.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Mark Hennings
May 3, 2016

Since H x = x k = 1 1 k ( k + x ) x > 0 H_x \; = \; x\sum_{k=1}^\infty \frac{1}{k(k+x)} \qquad \qquad x > 0 we have x H x = lim K x k = 1 K x k ( k + x ) = lim K x k = 1 K ( 1 k 1 k + x ) xH_x \; = \; \lim_{K\to\infty}x \sum_{k=1}^K \frac{x}{k(k+x)} \; = \; \lim_{K \to \infty}x \sum_{k=1}^K \left(\frac{1}{k} - \frac{1}{k+x}\right) and so, since 0 1 x k = 1 K ( 1 k 1 x + k ) d x = 0 1 ( x H K k = 1 K x x + k ) d x = 0 1 ( x H K K + k = 1 K k k + x ) d x = 1 2 H K K + k = 1 K k [ ln ( k + x ) ] 0 1 = 1 2 H K K + k = 1 K k ln ( k + 1 ) k = 1 K k ln k = 1 2 H K K + k = 2 K + 1 ( k 1 ) ln k k = 1 K k ln k = 1 2 H K K + K ln ( K + 1 ) k = 2 K ln k = 1 2 [ H K ln K ] K + K ln ( 1 + 1 K ) + ( K + 1 2 ) ln K ln K ! = 1 2 [ H K ln K ] + ln ( 1 + 1 K ) K ln ( K ! × e K K K + 1 2 ) \begin{array}{rcl} \displaystyle \int_0^1 x\sum_{k=1}^K\left(\frac{1}{k} - \frac{1}{x+k}\right)\,dx & = & \displaystyle \int_0^1 \left(xH_K - \sum_{k=1}^K \frac{x}{x+k}\right)\,dx \\ & = & \displaystyle\int_0^1 \left(xH_K - K + \sum_{k=1}^K \frac{k}{k+x}\right)\,dx \\ & = & \displaystyle\tfrac12H_K - K + \sum_{k=1}^K k\Big[\ln(k+x)\Big]_0^1 \\ & = & \displaystyle \tfrac12H_K - K + \sum_{k=1}^K k \ln(k+1) - \sum_{k=1}^K k \ln k \\ & = & \displaystyle \tfrac12H_K - K + \sum_{k=2}^{K+1}(k-1)\ln k - \sum_{k=1}^K k \ln k \\ & = & \displaystyle \tfrac12H_K - K + K\ln(K+1) - \sum_{k=2}^K \ln k \\ & = & \displaystyle \tfrac12\big[H_K - \ln K\big] - K + K\ln\big(1+\tfrac{1}{K}\big) + (K+\tfrac12)\ln K- \ln K! \\ & = & \displaystyle \tfrac12\big[H_K - \ln K\big] + \ln\big(1 + \tfrac{1}{K}\big)^K - \ln \left(\frac{K! \times e^K}{K^{K+\frac12}}\right) \end{array} we deduce (using the Monotone Convergence Theorem) that 0 1 x H x d x = lim K { 1 2 [ H K ln K ] + ln ( 1 + 1 K ) K ln ( K ! × e K K K + 1 2 ) } = 1 2 γ + 1 ln 2 π \int_0^1 x H_x\,dx \; = \; \lim_{K \to \infty}\Big\{\tfrac12\big[H_K - \ln K\big] + \ln\big(1 + \tfrac{1}{K}\big)^K - \ln \left(\frac{K! \times e^K}{K^{K+\frac12}}\right)\Big\} \; = \; \tfrac12\gamma + 1 - \ln\sqrt{2\pi} making the answer 1 + 2 + 2 = 5 1 + 2 + 2 = \boxed{5} .

Hassan Abdulla
Aug 6, 2019

0 1 x H x d x = 0 1 x ( ψ ( x + 1 ) + γ ) d x H x = ψ ( x + 1 ) + γ = 0 1 ( x ψ ( x + 1 ) + γ x ) d x = 0 1 ( x ψ ( x ) + 1 + γ x ) d x ψ ( x + 1 ) = ψ ( x ) + 1 x u = x d v = ψ ( x ) d u = d x v = ln ( Γ ( x ) ) 0 1 x ψ ( x ) = x ln ( Γ ( x ) ) 0 1 0 1 ln ( Γ ( x ) ) d x x ln ( Γ ( x ) ) 0 1 = 0 = 1 2 0 1 ln ( Γ ( x ) ) + ln ( Γ ( 1 x ) ) d x a b f ( x ) d x = a b f ( a + b x ) d x = 1 2 0 1 ln ( Γ ( x ) Γ ( 1 x ) ) d x = 1 2 0 1 ln ( π sin ( π x ) ) d x Euler’s reflection formula = 1 2 ( 0 1 ln ( π ) d x 0 1 ln ( sin ( π x ) ) d x ) = 1 2 ( ln ( π ) ( ln ( 2 ) ) ) = ln ( 2 π ) l e t u = π x and use symmetry back to original integral 0 1 x H x d x = ln ( 2 π ) + 1 + γ 2 \begin{aligned} &\int_0^1 x H_x dx &&= \int_0^1 x(\psi(x+1) + \gamma)dx && {\color{#D61F06} H_x = \psi(x+1) + \gamma} \\ &&&= \int_0^1 (x\psi(x+1) + \gamma \cdot x) dx\\ &&&= \int_0^1 ({\color{#3D99F6}x\psi(x)} + 1 + \gamma \cdot x) dx && {\color{#D61F06} \psi(x+1)=\psi(x) + \frac{1}{x} } \\ &&& {\color{#3D99F6}\begin{matrix} u=x & dv=\psi(x) \\ du= dx & v = \ln(\Gamma(x)) \end{matrix}} \\ & \color{#3D99F6} \int_0^1 x\psi(x) && \color{#3D99F6} = \left . x \ln(\Gamma(x)) \right |_0^1-\int_0^1 \ln(\Gamma(x)) dx && \color{#D61F06} \left . x \ln(\Gamma(x)) \right |_0^1 = 0\\ &&& \color{#3D99F6} = -\frac{1}{2}\int_0^1 \ln(\Gamma(x))+\ln(\Gamma(1-x)) dx && \color{#D61F06} \int_a^b f(x)dx=\int_a^b f(a+b-x)dx \\ &&& \color{#3D99F6} = -\frac{1}{2}\int_0^1 \ln(\Gamma(x) \Gamma(1-x)) dx \\ &&& \color{#3D99F6} = -\frac{1}{2}\int_0^1 \ln(\frac{\pi}{\sin(\pi x)}) dx && \color{#D61F06} \text{Euler's reflection formula}\\ &&& \color{#3D99F6} = -\frac{1}{2}\left (\int_0^1 \ln(\pi)dx - \int_0^1 \ln(\sin(\pi x)) dx \right ) \\ &&& \color{#3D99F6} = -\frac{1}{2}\left (\ln(\pi) - {\color{#D61F06} (-\ln(2))} \right )= -\ln(\sqrt{2 \pi}) && \color{#D61F06} let \ u=\pi x \text{ and use symmetry}\\ &&& \color{#20A900} \text{back to original integral} \\ &\int_0^1 x H_x dx && = {\color{#3D99F6} -\ln(\sqrt{2 \pi})} + 1 + \frac{\gamma}{2} \\ \end{aligned}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...